Estimation of Candida albicans ABC Transporter Behavior in Real-Time via Fluorescence - Szczepaniak, Joanna; Łukaszewicz, Marcin; Krasowska, Anna (Frontiers in Microbiology, 2015)
We present a fluorometric method for determining ABC transporter activity in the pathogenic fungus Candida albicans during different growth phases and in response to glucose. The carbocyanine dye diS-C3(3) was previously used to monitor plasma membrane potentials and test the influence of surface-active compounds in membrane polarization. We used diS-C3(3) to show changes in fluorescence kinetics that reflect changes in the activity of ABC transporters in C. albicans growth. Cdr1-GFP fluorescence, revealed that Cdr1p relocates to the inside of the cell after the early-log growth phase. Addition of glucose to the cell suspension resulted in Cdr1p transporter expression in the CDR2-knockout strain. We confirmed the diS-C3(3) results by standard RT-PCR and Western blotting.